Postoperative chemoradiotherapy for elderly patients with glioblastoma: worsening frailty or increasing survival? - Pinzi, Valentina (Translational Cancer Research, 2017)
Recently published by Perry and colleagues, the data of the trial (ClinicalTrials.gov number, NCT00482677) funded by the Canadian Cancer Society Research Institute (CCSRI), European Organisation for Research and Treatment of Cancer (EORTC) and by the Trans Tasman Radiation Oncology Group (Australia and New Zealand) (1) provided further insight into the role of combined chemoradiotherapy in 65 years of age or older patients with glioblastoma (GBM) and finally answer whether chemotherapy concomitant to radiotherapy (RT) could yield survival benefit or potentially impairing quality of life for these patients.